Vitamin D supplementation alleviates insulin resistance in prediabetic rats by modifying IRS-1 and PPARγ/NF-κB expressions - Krisnamurti, Desak Gede Budi; Louisa, Melva; Poerwaningsih, Erni H.; Tarigan, Tri Juli Edi; Soetikno, Vivian; Wibowo, Heri; Nugroho, Christian Marco Hadi (Frontiers in Endocrinology, 2023)
Background Prediabetes is a condition of intermediate hyperglycemia that may progress to type 2 diabetes. Vitamin D deficiency has been frequently linked to insulin resistance and diabetes. The study aimed to investigate the role of D supplementation and its possible mechanism of action on insulin resistance in prediabetic rats. Method The study was conducted on 24 male Wistar rats randomly divided into six healthy controls and 18 prediabetic rats. Prediabetic rats were induced with a high-fat and high-glucose diet (HFD-G) combined with a low dose of streptozotocin. Rats with the prediabetic condition were then randomized into three groups of 12-week treatment: one group that received no treatment, one that received vitamin D3 at 100 IU/kg BW, and one group that received vitamin D3 at 1000 IU/kg BW. The high-fat and high-glucose diets were continuously given throughout the twelve weeks of treatment. At the end of the supplementation period, glucose control parameters, inflammatory markers, and the expressions of IRS1, PPARg, NF-kB, and IRS1 were measured. Results Vitamin D3 dose-dependently improves glucose control parameters, as shown by the reduction of fasting blood glucose (FBG), oral glucose tolerance test (OGTT), glycated albumin, insulin levels, and markers of insulin resistance (HOMA-IR). Upon histological analysis, vitamin D supplementation resulted in a reduction of the islet of Langerhans degeneration. Vitamin D also enhanced the ratio of IL-6/IL-10, reduced IRS1 phosphorylation at Ser307, increased expression of PPAR gamma, and reduced phosphorylation of NF-KB p65 at Ser536. Conclusion Vitamin D supplementation reduces insulin resistance in prediabetic rats. The reduction might be due to the effects of vitamin D on IRS, PPARg, and NF-kB expression.